Introducing biomarkers for invasive fungal disease in haemato-oncology patients: a single-centre experience. Issue 7 (12th July 2022) - Martinelli, Anthony W.; Wright, Callum B.; Lopes, Marta S.; Swayne, Rosemary L.; Krishnamurthy, Pramila; Crawley, Charles; Uttenthal, Ben; Follows, George; Babar, Judith; Aliyu, Sani H.; Enoch, David A.; Sander, Clare R.
Abstract : Hypothesis/Gap Statement. The impacts of increased biomarker testing on antifungal prescribing have not yet been fully examined in a real-life setting. Objectives. Biomarkers for invasive fungal disease (IFD) have been shown to reduce antifungal prescriptions in neutropaenic haemato-oncology patients. Our study aimed to assess the real-life impacts of introducing a novel biomarker-based pathway, incorporating serum galactomannan and Aspergillus PCR, for pyrexial haemato-oncology admissions. Methods. Patients with neutropaenic fever were identified prospectively after introduction of the new pathway from 2013–2015. A historical group of neutropaenic patients who had blood cultures taken from 2009–2012 was generated for comparison. Clinical details, including demographics, underlying diagnosis, investigations, radiology and antimicrobial treatment were obtained. Results. Prospective data from 308 patients were compared to retrospective data from 302 patients. The proportion of patients prescribed an antifungal medication was unchanged by the pathway ( P =0.79), but the pattern was different, with more patients receiving targeted antifungals ( P =0.04). A negative serum galactomannan test was not sufficient evidence to withhold therapy, with 17.2% of these episodes felt to have possible or probable IFD using the European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group (EORTC/MSG) criteria. There was no difference in 30-day mortality ( P =0.21) or 1-year mortality ( P =0.57) following introduction of the pathway. Conclusions. Biomarkers can be used safely as part of a multidisciplinary approach to the diagnosis of IFD in neutropaenic haemato-oncology patients. Whilst they do not necessarily result in antifungal therapy being withheld, they can allow more confident diagnosis of IFD and more specific antifungal therapy in selected cases.